Exposing and re-placing leadership through workers inquiry. (February 2022) - Smolović Jones, Owain; Briley, George; Woodcock, Jamie
The literature on leadership place and space offers us an understanding of how the built environment, geography of location and socio-economic forces can coalesce to shape (and be shaped) by leadership practices. Missing thus far, however, is an account that constitutes leadership space and place through antagonism and struggle, crucial if we are to acknowledge the agency of workers in leadership practice. We therefore outline a workers inquiry approach that seeks to learn directly from the struggles of workers as they enact place and space through their particular, geographically situated practices. We do so through reading leadership studies, Marxist accounts of space and place, and workers' inquiries dialectically to draw out two practices that can offer a framework for both understanding the contribution of workers inquiry approaches to leadership but also to inform future studies. Our first practice of exposing is the drawing to the surface by workers inquiry of the oppressiveness, contradictions and absurdities of leadership discourse and practices of capital as they shape the places and spaces within which workers are exploited. Re-placing, on the other hand, offers workers' movements potentially emancipatory alternative forms of leadership, which re-shape and re-appropriate place and space.